Identification and Separation of Lead (II), Nickel (II), and Cobalt (II) on Silica Gel 60 F254 High-Performance Thin-Layer Chromatographic Plates with Mixed Aqueous Sodium Dodecyl Sulfate–Oxalic Acid Solvent System - Bhawani, Showkat Ahmad; Sufia, Hena; Mohamad Nasir, Bin Mohamad Ibrahim; Othman, Bin Sulaiman; Rokiah, Binti Hashim; Kok, San L. (Akadémiai Kiadó, 2012)
The chromatographic separation of three metal cations was performed on high-performance thin-layer plates (silica gel 60F254) with mixed sodium dodecyl sulphate (SDS) and oxalic acid. The effect of concentration of surfactant and additive effect of different carboxylic acids on the mobility of metal ions were investigated. The resolution of a mixture of Pb2+, Ni2+, and Co2+ was achieved by using 0.2 M SDS plus 0.08 M oxalic acid, 1:9, v/v as a solvent system. The developed method was utilized to identify these metal ions in different spiked water samples after their preliminary separation.